Comparative analysis of pain outcomes in operative versus diagnostic hysteroscopy: the role of menopausal status - Özkol, Vahit; Bornaun, Teymur (The European Research Journal, 2025)
Objectives: The study investigates the differential pain outcomes associated with operative and diagnostic hysteroscopy, with a focus on the influence of menopausal status on pain perception. This research aims to refine pain management strategies tailored to patient demographics in gynecological practices. Methods: A total of 200 patients undergoing hysteroscopy were systematically evaluated. Pain intensity was assessed using the Visual Analog Scale (VAS). The study distinguished between operative and diagnostic procedures, with particular attention to the effect of menopausal status on pain scores. Compliance with CONSORT guidelines was ensured, and relevant clinical trial registration numbers were included. Results: Pain scores did not significantly differ between operative and diagnostic hysteroscopies, suggesting that the invasiveness of the procedure might not directly correlate with pain perception. However, menopausal women reported significantly higher pain scores, indicating a possible increased sensitivity or decreased pain tolerance related to hormonal changes. Conclusions: The results affirm that existing pain management protocols effectively mitigate discomfort across different hysteroscopic procedures. Nonetheless, the distinct pain profiles of menopausal women warrant the development of customized pain management strategies. Enhancing analgesic approaches for this subgroup could improve patient care and outcomes in gynecological settings.